Magic, Cure, And Ancestors: An Ethno- Historical Investigation in North Malabar - Poyil, Manjula (Journal of Posthumanism, 2026)
Magic , Cure, and Ancestors: A Historical Investigation in North Malabar examines how forefathers' traditional healing practices cure diseases and improve both mental and physical health conditions of the ethnic folk of North Malabar. The study examines how charm, traditional curing practices, and ancestors served as a harmonizing system of knowledge and balance within ethnic communities. Sources for ethnic magical practices found in the ethnic folk memory, ritual rites, ethnic art, and oral traditions are not simply expressions or fantasies but part and parcel of the comprehensible traditional rationality deep-rooted in the ways of their ancestors and their eco-friendly lifestyle. The paper highlights the role of traditional healing practitioners, ritual functionaries, and ancestors in keeping this tradition a long-lasting one. The study pays attention to a profound understanding of the ethnic intangible heritage and the challenges it faces due to acculturation and fasting changing society.